2022
DOI: 10.3389/fpls.2022.978497
|View full text |Cite
|
Sign up to set email alerts
|

The combined influence of rootstock and vintage climate on the grape and wine flavonoids of Vitis vinifera L. cv. Cabernet Sauvignon in eastern China

Abstract: Rootstocks are commonly utilized owing to their resistance to abiotic and biotic stress in viticulture. This study evaluated the effects of three rootstocks (1103P, SO4, and 5A) on the Cabernet Sauvignon (CS) vine growth, and their berries and wines flavonoids profiles in four consecutive vintages. The results showed that 1103P increased the pruning weight of CS and decreased the anthocyanin concentration in berries and wines, especially in the vintages with more rainy and cloudy days. 5A tended to decrease th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
(80 reference statements)
2
2
0
Order By: Relevance
“…These results agree with the work of Pouget (1986), who clearly demonstrated that vines with large canopies, induced by the rootstock, tend to prolong fruit maturation, in comparison with vines grafted onto low vigor genotypes, which in turn tend to accelerate the maturation process. This trend has also been reported in other studies (Brighenti et al, 2011;Keller et al, 2011;Neal et al, 2014;Jogaiah et al, 2015;Han et al, 2022).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…These results agree with the work of Pouget (1986), who clearly demonstrated that vines with large canopies, induced by the rootstock, tend to prolong fruit maturation, in comparison with vines grafted onto low vigor genotypes, which in turn tend to accelerate the maturation process. This trend has also been reported in other studies (Brighenti et al, 2011;Keller et al, 2011;Neal et al, 2014;Jogaiah et al, 2015;Han et al, 2022).…”
Section: Resultssupporting
confidence: 89%
“…Regarding the maturation of 'Merlot', similar data were observed by Han et al (2022), which also reported the impact of rootstocks on total acidity and pH of the juice, without influencing soluble solids content. Nascimento et al (2022), evaluated the effects of different rootstocks on 'Magna' variety and they observed similar behavior for these variables.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…However, it is noteworthy that rootstock (Pt) had a significant effect on the accumulation of total flavonoids in MT pulp (Figure 3). Similar results have been observed in grapes [38] and apples [39]. Among the flavonoid components, we detected only naringin and rutin; neohesperidin and naringenin were not detected (Figure 4).…”
Section: Natural Variation and Rootstock Effect The Antioxidant Capac...supporting
confidence: 87%